A New Modulation Technique Using Double Transmission In Free Space Optical Communication for Access Network - SIMON KWANG THAI, ANG (SIMON ANG KWANG THAI, 2024)
In FSO communication links, the atmospheric turbulence has a significant impact on the quality of a laser beam where turbulence results in intensity scintillation, which can severely impair the operation of target designation and FSO communications systems. This research proposed the Double Transmission Balance Receiver (DTBR), a new approach for modulation technique in free-space optical communication. By utilize the Gaussian atmospheric channel analysis is the first step method. This factor will determine the trajectory of the research study and will restrict this strategy to implementing the calculations-related research. The second method is a mathematical derivation development where the new modulation technique is compared to conventional modulation techniques. The performance evaluation will investigate signal strength, signal threshold, signal-to-noise ratio, and bit error rate. In the meantime, the third method simulates the DTBR method using the OptiSystem software. This allows for an analysis close to actual FSO conditions, which can be validated with the theoretical portion. From the result shows that analysis from effective power, in strong turbulence condition the DTBR can improve approximately 50% of power received. For bit rate analysis, it can operate at higher bit rate of 10 Gbps (STM64) with the BER is approximately at 5.91 x 10-11 as compared to conventional ASK only at 2.77x 10-4. This gives percentage improvement about 175%. Meanwhile in distance analysis, the DTBR manage to achieve BER approximately 5.51 x 10-17 while conventional only 4.89 x 10-4. Thus, contribute improvement of 13 magnitude of BER or equivalent of 325%. Therefore, via the presented analysis the new proposed is have the better performance as compare to conventional ASK technique with new threshold at level zero ‘0’.